The Current Situation and Governance Strategies of Online Solicitation of Prostitution - Liu, Yilin; Zhang, Yi (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, the rapid advancement of the Internet has given rise to a plethora of new types of crimes, with online prostitution emerging as a prominent issue. The incidence of online prostitution cases has been steadily increasing, impacting societal norms and creating significant harm. In contrast to traditional forms of solicitation and prostitution, online activities are more clandestine, making investigations and evidence collection challenging. Given these challenges, it is crucial to examine the legal rights implicated in online prostitution and develop effective management strategies to deter and address such behavior. One approach involves strengthening the connection between the Administrative Penalty Act and criminal law to ensure appropriate consequences for offenders. Additionally, enhancing surveillance mechanisms for content dissemination is essential to curb the proliferation of online prostitution activities. By adopting a comprehensive approach that combines legal frameworks with robust enforcement measures, we can mitigate the negative effects of online prostitution and safeguard the integrity of our digital landscape.